Output peak control of nonhomogeneous markov jump system with unit-energy disturbance - Liu, Y.; Liu, F.; Teo, Kok Lay (Birkhaeuser Science, 2014)
This paper considers output peak controller design for discrete nonhomogeneous Markov jump systems under unit-energy disturbance. The mode-dependent output peak feedback controller is designed to ensure that the resulting closed-loop system is stochastically stable and the peak of the output is within a specified range. Furthermore, the optimal energy-to-peak gain indices of the mode-dependent and the mode-independent state feedback controllers are evaluated and compared. A numerical example is presented to illustrate the applicability of the results obtained.